2016
DOI: 10.1051/e3sconf/20160801005
|View full text |Cite
|
Sign up to set email alerts
|

Dry grinding of talc in a stirred ball mill

Abstract: ÖZ Karıştırmalı bilyalı değirmende (attritör), mikron altı ve nano boyutlu tanelerin öğütmede sergilediği davranış ve elde edilebilir en küçük tane boyutu süspansiyonun kararlılığından oldukça fazla etkilenmektedir. Bu çalışma kapsamında, yaş öğütmede talkın süspansiyon kararlılığı pH ölçümü ile araştırılmıştır. Elde edilen veriler doğrultusunda, karıştırmalı bilyalı değirmende belli bir süre sonunda boyutta çok fazla bir küçülme olmadığı ve ortalama ürün boyutunun (d 50) arttığı gözlenmiştir. Bunun asıl sebeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…In other words, the powder filling ratio was inversely proportional to the product size. In previous studies, the effect of interstitial filling ratio (U) was investigated in dry feldspar and mica grinding in a stirred ball mill by the author of this study [29][30][31], and similar results were observed. Figure 7 also shows that an increase in the powder filling ratio from 0.05 to 0.15 reduced specific surface area from 3.28 to 2.30 m 2 /g.…”
Section: The Influences Of Powder Filling Ratiosupporting
confidence: 71%
“…In other words, the powder filling ratio was inversely proportional to the product size. In previous studies, the effect of interstitial filling ratio (U) was investigated in dry feldspar and mica grinding in a stirred ball mill by the author of this study [29][30][31], and similar results were observed. Figure 7 also shows that an increase in the powder filling ratio from 0.05 to 0.15 reduced specific surface area from 3.28 to 2.30 m 2 /g.…”
Section: The Influences Of Powder Filling Ratiosupporting
confidence: 71%
“…Like the other authors, they also mentioned the optimum solids concentration was below 70% for stirred mill operation. Cayirli et al (2012) also supported the findings of the above authors while grinding Sodium Feldspar in a lab scale vertical stirred mill. Mankosa et al (1989) found an optimum slurry density of less than 60% when grinding coal in a vertical stirred mill.…”
Section: Solid Concentrationsupporting
confidence: 88%
“…They also mentioned that the slurry rheological behavior changes with an increase in grinding time due to the production of the fine particles. Cayirli et al (2012) tested the effect of grinding time of 30, 60, 90, 120 and 150 minutes in a batch laboratory pin stirred mill and found that energy consumption increased linearly with the grinding time. However, they did not find the optimum grinding time beyond which fines production is constant in the mill.…”
Section: Grinding Timementioning
confidence: 99%
“…Talc is one of the economic minerals that has several applications. The size of talc particles represents a crucial key in the success of various talc industrial applications (Cayirli, 2016; Kim et al, 2019). To produce the required particle size, mechanical grinding is commonly used for talc, as well as for different minerals (Senthilkumar and Akilamudhan, 2014).…”
Section: Introductionmentioning
confidence: 99%